Perinatal Outcome of Eclampsia in Dhaka Medical College Hospital - Alam, Irin Parveen; Akhter, Sayeba (Bangladesh Journal of Obstetrics & Gynaecology, 2009)
Objectives: The study was done with the objective to find the perinatal outcome in eclampsia patients and also to find out preventable causes of perinatal mortality and morbidity which are related to eclampsia. Materials & methods: This was a cross sectional observational study carried out in the Eclampsia unit in the Department of Obstetrics and Gynaecology in Dhaka Medical College Hospital during the period from February 2001 to July 2001. Results: Three hundred patients were selected for study. Three hundred mother's delivered 311 babies (11 sets of twins). Perinatal death(PND) which included stillbirth (SB) and early neonatal death (END) was 29%; stillbirth rate was 158/1000 live birth and early neonatal death rate was 132/1000 live births; 71% babies were born healthy. Maternal and fetal conditions were assessed and its relation with perinatal outcome was analyzed. Convulsion delivery interval > 12 hours, diastolic BP > 110mm Hg and Proteinuria > 3+ had significant higher perinatal death. (P<0.001, <0.01 and <0.001, respectively). Seventy percent babies had low birth weight. Among the live born neonates (n=262) 27.5% had jaundice, 34.7% had no complication and 15.6% had early neonatal death. Pre-maturity was common cause of early perinatal death (54%) and 39% death was due to asphyxia. Conclusion: Still birth, prematurity and birth asphyxia are important causes of perinatal loss in eclampsia, so early referral of eclampsia patients, early resuscitative measures and good neonatal care can improve perinatal outcome. doi: 10.3329/bjog.v23i1.3053 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(1) : 20-24